Efecto de cinco formas de polinización en el rendimiento y calidad de fruto del cultivo de Passiflora edulis var. flavicarpa en Laredo, La Libertad - Villa Plasencia, Edy David (2018)
The present research work in passion fruit was carried out in Laredo district, Trujillo province of Trujillo, La Libertad region to contribute to its profitability by increasing production in the new areas of the cultivation of this fruit. Treatments were five types of pollination: natural pollination, directed manual pollination, spontaneous self-pollination, directed manual self-pollination and geitonogamy. The experimental design corresponded to complete randomized blocks with four repetitions. Characteristics evaluated were number, weight, length and diameter of fruit, number of seeds per fruit, weight of pulp per fruit, volume of juice and brix degrees. Spontaneous self-pollination, directed manual self-pollination and geitonogamy do not produced fruit, confirming the high degree of self-incompatibility present in passion fruit under Laredo conditions._x000D_ Natural pollination and directed manual pollination treatments producedthe same number (75% of fruits achieved), weight (231.2 g), lenghy (9.49 cm) and diameter of fruit (8.09 cm), as well as the same number of seeds per fruit (414.25), weight of pulp per fruit (76.57 g) and degrees brix (13.140). However, natural pollination showed a greater volume of juice with value of 84.6 ml.